The Implementation of Authentic Assessment in Arabic Language Learning - Jannah, Siti Alfiatul; Bin Madi, Faisol Nasar; Rosyid, Abdur; Muhamad, Ahmad; Husin, Saifuddin Ahmad (Jurnal Al-Maqoyis, 2024)
This study was conducted to investigate the implementation of Authentic Assessment in Arabic and the obstacles experienced by teachers. This study used a descriptive qualitative approach. The data collection techniques were observation, interviews and documentation. The technique used is the analyzing the data was the Miles and Huberman model, namely data collection, data reduction, data presentation, and conclusions. The result of this study showed that there where three aspects of student assessment, namely the cognitive realm which includes oral, written, and assignment-based evaluations with oral; the affective realm which assesses student attendance through a liaison attendance system and evaluates student attitudes; the psychomotor realm which involves practical assessment by making calligraphy in groups. The obstacles faced were the absence of a language lab, limited time, and uneven student backgrounds. The benefits of this authentic assessment are that everything students do is valuable and gets points. Students can express ideas. Students are passionate about learning Arabic. Students can know and interpret their own scores according to their behavior and activeness in class.